PENGARUH KINERJA PETUGAS APRON MOVEMENT CONTROL (AMC) TERHADAP KEDISIPLINAN KERJA PETUGAS GROUND HANDLING DI APRON BANDAR UDARA INTERNASIONAL ADI SOEMARMO BOYOLALI - Adela Fauziah Mufida (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
ABSTRACT, The achievement of the achievement of a particular job is a form of a performance. Thus, work performance is the stage of work achievement by an individual in an organization. Some of the cases that have occurred at Adi Soermarmo Boyolali International Airport, one of which is negligence by Ground Handling officers, namely, the lack of awareness of Ground Handling officers in using PPE (personal protective equipment) so that there needs to be disciplinary action and the role of AMC officers to always behave decisively when there is an act violations committed by Ground Handling officers in order to anticipate unwanted things. The purpose of this study was to determine the effect of the performance of AMC officers and how much influence the performance of AMC officers had on the discipline of Ground Handling officers. This study uses one independent variable, namely the performance of AMC officers and one dependent variable, namely the discipline of Ground Handling officers. The method in this study is a quantitative descriptive method, while the sampling technique in this study is non-probability sampling. Collecting data using questionnaires and observation methods. In analyzing the instrument data used is the test of validity and reliability. To test the hypothesis of this study using simple linear regression data analysis, determination test, and t test. The results of the research show that the indicators in this study are valid and reliable. In the hypothesis test, the effect of the performance of AMC officers has a positive and significant influence on the work discipline of Ground Handling officers at Adi Soemarmo Boyolali International Airport Apron. The results of the determination test in this study obtained a determinant value of 0.699 which means that the magnitude of the influence of the performance variable of AMC officers (X) on the work discipline variable of Ground Handling officers (Y) is 69.9%.